Visual Disturbances in Patients With Acute Methanol Poisoning: A Cross-sectional Study: Acute methanol poisoning and visual disturbances - Mousavi-Roknabadi, Razieh Sadat; Alibeigi, Mahdi; Sharifi, Mehrdad; Mousavi-Roknabadi, Reyhaneh Sadat; Beizavi, Zahra (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Methanol poisoning is a serious problem in public health, especially in developing countries. The present study aimed to evaluate the incidence of visual disturbances in patients with acute methanol poisoning in the south of Iran. Methods: This cross-sectional study (from 21/March/2014 to 21/March/2019) was conducted on all adult patients’ medical records who were referred to Ali-Asghar Hospital in Shiraz City, Iran, with acute methanol poisoning. The required data were collected using a data-gathering form and were then analyzed. Results: Twenty male patients were enrolled in this research, with Mean±SD age of 33.15±10.40 years. Visual disturbances were observed in 15(75%) of the study subjects, as the most common clinical manifestations. Blurred vision (40%) and blindness (35%) were the most frequent visual disturbances in the study participants. None of the study subjects reported photophobia. The explored variables did not differ between patients with visual disturbances and those without visual disturbances. Only one patient who encountered blindness was expired. Conclusion: The incidence of visual disturbances in the study patients with acute methanol poisoning was higher than that of similar studies.